Manajemen Laba Melalui Islamic Corporate Governance sebagai Pemoderasi pada Bank Umum Syariah: Capital, Asset Quality, Management, Earnings, Liquidity - Anisa Rahmalina (Universitas Putra Indonesia YPTK Padang, 2021)
This study aims to determine how the influence of earnings management through Islamic corporate governance as a moderating variable in Islamic commercial banks registered with the OJK: Capital, Asset Quality, Management, Earnings, Liquidity.The sampling technique used was the purposive sampling method. This research uses quantitative research with secondary data in the form of panels. The sample used was 12 Islamic commercial banks for the 2016-2020 period, Based on the results of the first hypothesis test from the partial regression results, it shows that capital has a significant effect on earnings management. The second hypothesis shows that Asset Quality has a significant effect on earnings management. The third hypothesis shows that management has no significant effect on earnings management. The fourth hypothesis shows that Earnings has a significant effect on earnings management. The fifth hypothesis shows that liquidity has no significant effect on earnings management. The sixth hypothesis shows that Islamic Corporate Governance is able to moderate the positive and significant influence of Capital on Earnings Management. The seventh hypothesis shows that Islamic Corporate Governance is able to moderate the positive and significant influence of Asset Quality on Earnings Management. The eighth hypothesis shows that Islamic Corporate Governance is not able to moderate the positive and significant influence of Management on Earnings Management. Hypothesis nine shows that Islamic Corporate Governance is not able to moderate the positive and significant effect of Earnings on Earnings Management. Hypothesis nine shows that Islamic Corporate Governance is not able to moderate the positive and significant effect of Liquidity on Earnings Management.